Spectroscopically Resolved Partial Phase Curve of the Rapid Heating and Cooling of the Highly Eccentric Hot Jupiter HAT-P-2b with WFC3 - Bob Jacobs; Jean-Michel Désert; Nikole Lewis; Ryan C. Challener; L. C. Mayorga; Zoë L. de Beurs; Vivien Parmentier; Kevin B. Stevenson; Julien de Wit; Saugata Barat; Jonathan Fortney; Tiffany Kataria; et al. (The Astronomical Journal)
The extreme environments of transiting close-in exoplanets in highly eccentric orbits are ideal for testing exoclimate physics. Spectroscopically resolved phase curves not only allow for the characterization of their thermal response to irradiation changes but also unveil phase-dependent atmospheric chemistry and dynamics. We observed a partial phase curve of the highly eccentric close-in giant planet HAT-P-2b ( e  = 0.51, M  = 9 M _Jup ) with the Wide Field Camera 3 aboard the Hubble Space Telescope. Using these data, we updated the planet's orbital parameters and radius and retrieved high-frequency pulsations consistent with the planet-induced pulsations reported in Spitzer data. We found that the peak in planetary flux occurred at 6.7 ± 0.6 hr after periastron, with heating and cooling timescales of $9.{0}_{-2.1}^{+3.5}$ hr and $3.{6}_{-0.6}^{+0.7}$ hr, respectively. We compare the light curve to various 1D and 3D forward models, varying the planet's chemical composition. The strong contrast in flux increase and decrease timescales before and after periapse indicates an opacity term that emerges during the planet's heating phase, potentially due to more H ^− than expected from chemical equilibrium models. The phase-resolved spectra are largely featureless, which we interpret as indicative of an inhomogeneous dayside. However, we identified an anomalously high flux in the spectroscopic bin coinciding with the hydrogen Pa β line, and that is likely connected to the planet's orbit. We interpret this as due to shock heating of the upper atmosphere given the short timescale involved, or evidence for other star−planet interactions.